(untitled) (Experimental biology, 2024)
Cyclachaena xanthiifolia (Nuttall) Fresenius, an invasive species belonging to the "transformer" species capable of radically transforming natural plant communities and influencing the taxonomic and phylogenetic uniqueness of regional floras, was found for the first time on the territory of the Aktobe region. The plant was found on the territory of Aktobe , three cenopopulations with C. xanthiifolia have been described. All the studied cenopopulations are small-species containing 7-9 species and consist of ruderal species. In all three cenopopulations, C. xanthiifolia together with Chenopodium album are the dominant plant communities., the partial projective coverage is 20%., the density in populations is from 12.0±3.1 to 17.0±2.6 pcs/m2, the height varies from 80.0±9.3 to 138±14.0 cm. The activity of C. xanthiifolia is very high and is second only to C. album.